Stability evaluation of earth‐abundant metal‐based polyoxometalate electrocatalysts for oxygen evolution reaction towards industrial PEM electrolysis at high current densities. Issue 3 (6th July 2021) - Vetter, Kim‐Marie; Aring da Silva Ramos Mauro, Camila; Reinisch, David; Reichbauer, Thomas; Martić, Nemanja; Jandl, Christian; Hinrichsen, Olaf; Schmid, Günter
Abstract: We investigated the cobalt polyoxometalate catalyst Ba8 [Co9 (H2 O)6 (OH)3 (HPO4 )2 (PW9 O34 )3 ] in oxygen evolution reaction for large‐scale water electrolysis. The catalyst was characterized, yielding BET surfaces (8.37 m 2 /g), crystal water content (8.38%, 44 H2 O), elemental analyses and single crystal structures (space group P1̅, a = 19.901(4) Å, b = 21.177(4) Å, c = 24.036(5) Å, α = 92.689(7)°, β = 108.73(7)°, γ = 117.137(6)°, Co9 Na16 O196.05 P5 W27, V = 8310(3) Å 2 with z = 2; R 2 final = 0.001). The catalyst was integrated in an industrially applicable membrane electrode assembly and electrochemically characterized. Polarization studies revealed catalyst dissolution in situ, visible as a current density peak (32.2 mA/cm 2, 2.2 V) with subsequent collapse (<5 mA/cm 2 ). Galvanostatic experiments showed voltage increase from 2.5 to > 10 V at 10 mA/cm 2 tracing back to acid‐mediated decomposition of the anionic POM oxide framework. We deduced insufficient thermodynamic as well as kinetic stability for industrial requirements in PEM water electrolysis. Abstract :